تطوير وحدة تعليمية في مبحث العلوم وفق منحى -ستيم- وفاعليتها في تنمية مهارات حل المسائل العلمية - ديانه, عزام; عقل, مجدي (جامعة الوادي - University of Eloued, 2022)
ملخص: هدف البحث الحالي إلى تطوير وحدة تعليمية في مبحث العلوم وفق منحى ستيم وفاعليتها في تنمية مهارات حل المسائل العلمية لدى طالبات الصف السابع الأساسي، ولهذا الغرض قام الباحثان باستخدام المنهج الوصفي التحليلي، والمنهج الوصفي التطويري، والمنهج شبه تجريبي لمجموعتين تجريبية وضابطة أجري عليهما القياس القبلي والبعدي للوصول إلى نتائج البحث، حيث طبق البحث على 70 طالبة من طالبات الصف السابع الأساسي بمدرسة السيدة رقية العلمي (ب)، وتكونت أدوات البحث من اختبار مهارات حل المسائل العلمية، وأظهرت النتائج وجود فروق ذات دلالة إحصائية عند مستوى (α=0.05)بين متوسطي درجات الطالبات في المجموعتين في اختبار مهارات حل المسائل العلمية البعدي لصالح المجموعة التجريبية، كما بينت النتائج أن منحى ستيم يحقق فاعلية تزيد عن (1.2) وفقًا للكسب المعدل لبلاك في تنمية مهارات حل المسائل العلمية لدى طالبات الصف السابع الأساسي في اختبار مهارات حل المسائل العلمية. Abstract: The currentre se ar chaims to developan education al unit in science subject according to STEAM approach and its effectiveness in developing scientific problem-solvingskills amon gseventh grade students. For this purpose, the researchersused the descriptive analytical method, the descriptive developmental method, and the quasi-experimental method for two groups (experimental group and control group), The research was applied to 70 female students of the seventh grade at Ruqayya Al- Alami school (B). The research toolsconsisted of scientific problem-sol vings kills tests whi chwasappliedbe fore and after the experiment. The results of the studyrevealed thatthereweresignifi cantstatistical differences at the level (α= 0.05) between the average scores of the two groups students in the post test of the scientific problem-solvin gskills in favor of the experiment al group. The results alse show edthat STEAM appro chachieves an effectiveness of more than (1.2) according to the average black gain in developing scientific problem-solvingskills for seventh grade students.
مقال
Keywords: تطوير وحدة تعليمية؛ مهارات حل المسائل العلمية; STEAM approach; development of educational unit; scientific problem-solvingskills